2008
DOI: 10.2337/dc08-s273
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Complications of Childhood Obesity

Abstract: The growing number of obese children and adolescents across the world creates a diagnostic challenge to caregivers. The early clinical manifestations of abnormalities related to childhood obesity, attributed to obesity-driven insulin resistance, are impaired glucose metabolism and nonalcoholic fatty liver disease. Both have no symptoms and demand a high index of suspicion and the proper choice of tests for establishing the diagnosis. The clinician should gather information derived from thoroughly taken history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
113
0
11

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(131 citation statements)
references
References 79 publications
(52 reference statements)
5
113
0
11
Order By: Relevance
“…25,26 In our study, we found a higher mean waist circumference among patients with hepatic steatosis. These data warrant and support the investigation of metabolic syndrome and hepatic steatosis in these children and adolescents.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…25,26 In our study, we found a higher mean waist circumference among patients with hepatic steatosis. These data warrant and support the investigation of metabolic syndrome and hepatic steatosis in these children and adolescents.…”
Section: Discussionsupporting
confidence: 55%
“…25,26 In order to test this relationship, Fishbein et al 22 used magnetic resonance imaging to assess 39 obese patients aged 6 to 18 years old, with hepatomegaly and hypertransaminasemia. The authors identified a correlation of hepatic fat fraction with visceral adiposity, but the same was not true with regard to subcutaneous adiposity and degree of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…An obesity-related profile of inflammation and adipocyte dysfunction is often found in parallel with impairments in lipid metabolism (21). Elevated FFA are thought to play an important role, since higher circulating fatty acids may induce intramyocellular lipid accumulation, directly inducing IR in skeletal muscle and impairing substrate utilization (22).…”
Section: Metabolism In Child Obesity Interventionmentioning
confidence: 99%
“…Currently, 24% of children ages two to five and 33% of children ages six to 11 are overweight or obese (1), putting them at risk for adolescent and adult obesity and co-morbid disease (2,3). Particularly at risk are Mexican-American children, for whom elevated body mass indices are found in 30% of two to five year olds and in 43% of six to 11 year olds (1).…”
Section: Introductionmentioning
confidence: 99%